Continued presence of enrofloxacin residues in feathers of broiler parent stock based on quantitative UHPLC-MS/MS detection - Moniek Ringenier; Marc Cherlet; Jeroen Dewulf; Mathias Devreese (Poultry Science)
Fluoroquinolones (FQ) are critically important antimicrobials. When broilers are treated with FQs, residues of these compounds can accumulate in their feathers, posing potential risks if feathers are repurposed, such as for use in animal feed. The aim of this study was to determine the residue depletion profiles of enrofloxacin (ENR) and its metabolite ciprofloxacin (CIP) in broiler parent stock feathers by using a sensitive UHPLC-MS/MS method. The total antibiotic residue concentration was determined. An experimental study was conducted with a treatment group and a control group. In the treatment group, fifty broiler parent stock were administered ENR for three consecutive days at 22.5 weeks of age, with four individual feathers analysed per animal at different timepoints after administration. After 15 weeks, all animals had ENR and CIP concentrations above the limit of quantification (LOQ) of 5 ng/g feather. ENR concentrations remained relatively stable throughout the observation period. For CIP, an initial rapid decline in concentration was observed, followed by a steady-state phase. Additionally, CIP concentrations were considerably lower than those of ENR. For both ENR and CIP the within-animal variance in residue levels was higher than the variability in mean residue levels across different animals sampled at the same timepoint. In conclusion, ENR and CIP demonstrate high stability in broiler parent stock feathers and can be detected for at least 15 weeks post-treatment. These findings highlight the persisting nature of FQ residues in feathers, underscoring the need for caution when considering the reuse of feathers in agricultural or industrial applications to prevent the development of antimicrobial resistance.